Financial Literacy, Risk Aversion, Financial Performance, and Innovative Behavior in Indonesian SMEs - Dwiputri, Rachmaniar Myrianda; Suyono, Eko; Laksana, Rio Dhani; Febriyanto (The Journal of Behavioral Science, 2023)
Lampung is one of the provinces that makes a major contribution to the Indonesian economy. The aim was to investigate the relationship between financial literacy and risk aversion on financial performance with innovative behavior as the mediating variable. The population were the SMEs in Lampung and a sample of 284 were selected. Structural equation modeling was used to test the research hypothesis. The research findings show that financial literacy had a positive direct effect on financial performance (β = .27, p = .006), risk aversion had a positive direct effect on financial performance (β = .21, p = .000), risk aversion, which had a positive direct effect on innovative behavior (β = .16, p = .005). Financial literacy was found to had a positive direct effect on innovative behavior (β = .73, p = .000); and innovative behavior had a positive direct effect on financial performance (β = .39, p = .000). When innovative behavior entered the relationship between financial literacy and financial performance, the direct effect (β = .04, p = .000) was significant. When innovative behavior was introduced into the link between risk aversion and financial success, the direct effect was significant (β = .34, p = .01). As a result, innovative behavior is regarded as a moderator of financial literacy and risk aversion on financial performance. This study elaborates on the ways that SME owners can improve their financial success by enhancing their financial literacy and embracing innovative behaviors that will ultimately benefit their business.